Identification and Potential of Yellow Root Plants in the Pining Forest Area, Gayo Lues Regency - Essy Harnelly; Al Wahid Ariga; Astri Winda Siregar (Jurnal Bioleuser, 2024)
Gayo Lues Regency, especially Pining District, has the most diverse and productive forest area with biodiversity, one of the types of plants used as medicinal materials is yellow-fruited moonseed. The study aims to obtain information about the types of yellow-fruited moonseeds and the potential for many types of yellow-fruited moonseeds found in the Bur Kaladurin Other Use Area (APL), Pining District, Gayo Lues Regency. Data collection was carried out by systematic sampling method to describe population conditions, data on each type of yellow-fruited moonseed plant, yellow-fruited moonseed diameter data and data on the number of yellow-fruited moonseeds found. 2 types of yellow-fruited moonseeds, namely Fibraurea tinctoria and Arcangelisia flava, were found as many as 1675 individuals at the study site from 56 specified sampling plots. The highest densities in each plot found were Fibraurea tinctoria with a density of 613 individuals/ha and Arcangelisia flava 135 individuals/ha. The highest diameter class frequency found from the 2.66 – 4.26 cm class was 452 individuals from the Fibraurea tinctoria and Arcangelisia flava species as many as 102 individuals from the 2.55 – 3.92 cm diameter class.